Hubungan Pengetahuan Ibu Hamil Tentang Anemia Defisiensi Besi Terhadap Kepatuhan Mengkonsumsi Tablet Zat Besi - Agustina; Girsang, Elizabeth; Tambunan, Ronald (Jurnal Kedokteran Methodist, 2021)
Background: Maternal mortality rate in Indonesia is still quite high compared to other ASEAN countries. Anemia in pregnancy is one of the indirect causes of death in pregnant women. It is estimated that more than 38% of pregnant women worldwide are anemic. Half of these anemia sufferers are assumed to be the result of iron deficiency. Pregnant women who have good knowledge about the importance of iron and the consequences that are caused if iron deficiency in pregnancy will result in obedient actions in consuming iron tablets. In Indonesia, the government program requires pregnant women to consume 1 tablet of iron a day at least 90 tablets during pregnancy. Methods: This type of research uses the literature study method or literature review with a maximum journal publication period of 5 years from 2015 to 2020. The population in this study were pregnant women who received iron tablets. Results: The results of this study indicate that there is a relationship between the knowledge of pregnant women about iron deficiency anemia and adherence to consuming iron tablets. Suggestion: For health workers to continue to provide health education to pregnant women about the importance of adherence to taking iron tablets to prevent iron deficiency anemia during pregnancy.